1992
DOI: 10.1007/bf01201948
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of steroid 11-hydroxylation activity ofCunninghamella elegans protoplasts in organic osmotic stabilizers

Abstract: Protoplasts ofCunninghamella elegans, showing 11α-, and 11β-hydroxylating ability of Substance S, preserved high transformation activity when dispersed in glucose-enriched, organic osmotic stabilizers. A joint action of polyoxins and 2-deoxy-D-glucose was necessary to prevent regeneration of the cell wall in long-lasting experiments. Stabilized and active, dispersed protoplasts may be an alternative research model for studying the function of the cell wall and intracellular metabolic pool constituents in stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…It is worth mentioning that the removal of chitin, an eukaryotic cell wall structure analogous to the prokaryotic peptidoglycan (ROGERS et al 1980), resulted also in greater steroid transformation rate of protoplasts, which has been shown in our previous papers (SEDLACZEK eta/. 1984, DLUGONSKI et al 1992.…”
Section: Discussionsupporting
confidence: 54%
“…It is worth mentioning that the removal of chitin, an eukaryotic cell wall structure analogous to the prokaryotic peptidoglycan (ROGERS et al 1980), resulted also in greater steroid transformation rate of protoplasts, which has been shown in our previous papers (SEDLACZEK eta/. 1984, DLUGONSKI et al 1992.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have been reported on immobilization techniques applied to filamentous fungi (Pakula and Freeman 1996;Dlugonski et al 1997) but little is known about the potential of biofilms (Harding et al 2009). Pakula and Freeman (1996) showed that a stainless steel mesh was required to catch mycelium fragments and start a gradual biofilm development in a continuous biofilm bioreactor for an oil-degrading filamentous fungus, Tyromyces sambuceus.…”
Section: Resultsmentioning
confidence: 99%